2018
DOI: 10.1002/ijc.31379
|View full text |Cite
|
Sign up to set email alerts
|

CLCA2 epigenetic regulation by CTBP1, HDACs, ZEB1, EP300 and miR‐196b‐5p impacts prostate cancer cell adhesion and EMT in metabolic syndrome disease

Abstract: Prostate cancer (PCa) is the most common cancer among men. Metabolic syndrome (MeS) is associated with increased PCa aggressiveness and recurrence. Previously, we proposed C-terminal binding protein 1 (CTBP1), a transcriptional co-repressor, as a molecular link between these two conditions. Notably, CTBP1 depletion decreased PCa growth in MeS mice. The aim of this study was to investigate the molecular mechanisms that explain the link between MeS and PCa mediated by CTBP1. We found that CTBP1 repressed chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…reduced UBQLN1 expression can cause enhanced cell migration and invasion, actin cytoskeleton rearrangements, and stimulation of the epithelial-mesenchymal transition (eMT) (42,43). Scholars have revealed that cTBP1 is carcinogenic in Pca and other adenomas, and overexpression of cTBP1 is thought to be involved in cell survival, proliferation, migration, invasion, and eMT (44)(45)(46). TriM27 was initially considered to be part of a fusion gene reT (rearranged during transfection), which is a proto-oncogene that is upregulated in multitudinal cancers, including PCa (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…reduced UBQLN1 expression can cause enhanced cell migration and invasion, actin cytoskeleton rearrangements, and stimulation of the epithelial-mesenchymal transition (eMT) (42,43). Scholars have revealed that cTBP1 is carcinogenic in Pca and other adenomas, and overexpression of cTBP1 is thought to be involved in cell survival, proliferation, migration, invasion, and eMT (44)(45)(46). TriM27 was initially considered to be part of a fusion gene reT (rearranged during transfection), which is a proto-oncogene that is upregulated in multitudinal cancers, including PCa (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CLCA2 decreases nasopharyngeal and breast tumourigenesis in vivo [ 307 , 312 , 315 ]. Similarly, CLCA2 depletion increases the number of circulating prostate tumour cells in mice [ 316 ]. At a cellular level, CLCA2 inhibits Wnt signalling [ 317 ], decreases invasion [ 315 ], inhibits proliferation [ 312 ], induces transcellular adhesion [ 316 ], inhibits epithelial-to-mesenchymal transition [ 312 , 316 ], induces differentiation [ 316 , 318 ], inhibits focal adhesion kinase [ 312 , 319 ] and induces p53-mediated cellular senescence [ 320 ].…”
Section: − Channelsmentioning
confidence: 99%
“…Similarly, CLCA2 depletion increases the number of circulating prostate tumour cells in mice [ 316 ]. At a cellular level, CLCA2 inhibits Wnt signalling [ 317 ], decreases invasion [ 315 ], inhibits proliferation [ 312 ], induces transcellular adhesion [ 316 ], inhibits epithelial-to-mesenchymal transition [ 312 , 316 ], induces differentiation [ 316 , 318 ], inhibits focal adhesion kinase [ 312 , 319 ] and induces p53-mediated cellular senescence [ 320 ]. The ability of CLCA2 to inhibit cancer cell migration appears to be I Cl independent, as inhibiting I Cl has a further anti-migratory effect in cells expressing CLCA2 as well as having an anti-migratory effect in cells not expressing CLCA2 [ 312 ].…”
Section: − Channelsmentioning
confidence: 99%
“…Thus, we identified novel pathways regulated by CTBP1 on a MeS environment [4,5]. CTBP1 depletion in androgeninsensitive PCa xenografts from HFD-fed mice affects the expression of genes and microRNAs (miRNAs) involved in hormone biosynthesis, olfactory signaling, and cell adhesion pathways, impacting in PCa development and progression [6][7][8]. Additionally, an androgen-sensitive PCa and MeS-like mice model allowed us to determine that MeS significantly increased tumor growth.…”
Section: Introductionmentioning
confidence: 99%